171k views
0 votes
What is the solution to the following system of equations?

What is the solution to the following system of equations?-example-1
User JustTB
by
5.4k points

2 Answers

6 votes

Answer:

X= 2 and Y=1

Explanation:

✯Hello✯

↪ So you know what y is so you can substitute into -2x-3y=-7

↪ -20x+33=-7 (thats after you expand the brackets)

↪ -20x=40

↪ this means that x=2. Therefore if u substitute y=1 and its on the options

❤Gianna❤

User Hlscalon
by
5.2k points
7 votes

Answer:

D. (2,1)

Explanation:

Fill in the value for y from the first eq (6x-11) into the second:

-2x - 3(6x-11) = -7

Now simplify:

-2x -18x + 33 = -7

-20x = -7-33

20x = 40

x = 2

Now that we have x, plug it into the top eq to get y:

y = 6*2 - 11 = 1

Et voila, x=2 and y=1, so the solution is (2,1).

User DavidW
by
5.7k points